Perawatan Bahan Pustaka di Perpustakaan Universitas Negeri Padang - Salman, Mardio; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper discusses the treatment of Library Materials in the Library of the State University of Padang, The purpose of this is Mecca (1) describe the factors damage library materials in the library of the State University of Padang (2) describe preventing damage library materials in the Library of the State University of Padang. Based on data collected through direct observation and interviews with staff how Libraries in Padang State University Libraries. It can be concluded: (1) the damaged library materials in the Library of the State University of Padang is a book, a collection of references, such as the periodic collection of journals and tabloids. (2) Factors damage library materials in the Library of the State University of Padang are biological factors and human factors. In order maintenance activities of library materials is expected to run well fields should State University Libraries (1) increase the resources in order to implement the activities of nurses librarian library materials properly. (2) maintenance activities of library materials not only reproductive activities, restoration and binding alone but all activities related to the care of library materials. Keywords: library materials; preservation